Social Network, Language Use and Language Ability among the Kejaman Community, Malaysia - Amee, Joan (UNIVERSITI MALAYSIA SARAWAK, 2022)
The Kejaman community is a small indigenous group living in the interior of Belaga, along the Balui River, in the Kapit Division of Sarawak, Malaysia. This study investigated the social network, language use and language ability among the Kejaman Community in Malaysia. The specific objectives of the study were to (1) compare the use of Kejaman to Malay, English, Chinese, Iban, Kayan, and Mixed Language by the three generations of Kejaman speakers; (2) determine the language ability of the three generations of Kejaman speakers to speak Kejaman, Malay, English, Iban, Kayan, and Mixed Language, and (3) compare the generational differences in the social network patterns of the Kejaman community. This study involved three generations of Kejaman speakers from two longhouses (Rumah Kejaman Neh Long Litten and Rumah Kejaman Ba Segaham) in Belaga. Data were collected from 123 participants through a questionnaire survey. The study employed Milroy's (1987) framework for social network analysis. In terms of language use, the study found that Mixed Language had the highest percentage of users, followed by the Kejaman language and the Iban language. Languages with the lowest percentage of users were Malay, English, Kayan and Chinese. The results of the study indicate that the older generation of the Kejaman community still speaks their native language, while the younger generation is switching to other languages. Additionally, findings from this study found there was a shift from monolingualism to multilingualism across three generations in the Kejaman community. Language ability varied significantly between the older and younger generations. The first and second generation had higher abilities in using their native language than Malay, English, Iban, Kayan, and Mixed Language. As for the third generation, their ability to speak their native language has significantly declined. Based on the analysis of the social networks for the Kejaman community, the participants had more exchange networks than interactive networks. The exchange networks played a significant role in matters concerning families, money, properties, financial matters, as well as matters related to their cultural traditions and customs, such as funerals, deaths, and taboos. Interactive networks dominated matters related to health, grocery shopping, ICT, and work. In terms of density and multiplexity, results showed there were only slight differences between the three generations. All three generations had low density scores, indicating that they had few social networks. Results from multiplexity analysis showed that the majority of participants had uniplex social networks. Based on a four-matrix quadrant chart, the Kejaman community involved in this study falls into two quadrants; Quadrant 3 (Low density, Uniplex) and Quadrant 4 (High density, Uniplex).